GRADED CRITERIA OF DIAGNOSTICS AND PREDICTION OF CENTRAL SEROUS CHORIORETINOPATHY OUTCOME - A. G. Shchuko; A. N. Zlobina; V. V. Bukina; A. A. Shchuko (Acta Biomedica Scientifica, 2016)
Present concept of central serous chorioretinopathy classification does not reflect the true picture of the pathological process. The purpose of the study was the development of diagnostic criteria of central serous chorioretinopathy clinical forms and basing on that extend and optimize its classification with assessment of risk factors and prognosis of disease. Full ophthalmologic and somatic examination of 56 men with central serous chorioretinopathy was made. Focal laser coagulation was performed in patients with fluorescein leakage and local injury of pigment epithelium by angiographic data (22 patients). In the case of extended damage of pigment epithelium and diffuse leakage of fluorescein (23 people) transpupillary thermotherapy of optical disk was conducted. Detailed expert evaluation of retinal changes by fluorescein angiographic data allowed dividing the patients into 3 groups. The main criterion for the division was the damaged area of the pigment epithelium: group 1 - central serous chorioretinopathy with local injury of pigment epithelium (with leakage point); group 2 - central serous chorioretinopathy with extensive damage of pigment epithelium with diffuse leakage; group 3 - central serous chorioretinopathy with extensive damage of pigment epithelium combined with leakage point (recurrence of leakage). The results of our study brought us to the following conclusion. Development of new classification criteria of the disease allows to construct a more specific algorithm of therapeutic measures and to determine prognosis of central serous chorioretinopathy already at the stage of diagnostics.